2010
DOI: 10.1111/j.1475-097x.2010.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary oedema in healthy SCUBA divers: new physiopathological pathways

Abstract: Immersion, body cooling, hyperoxia, increased hydrostatic pressure and strenuous exercise likely combine to induce pulmonary oedema in patients without cardiac disease. This study underlines new physiopathological tracks related to the frequent occurrence of symptoms noticed in the last part of the ascent and a higher incidence in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 27 publications
1
32
2
Order By: Relevance
“…The single, very small, relevant study only studied patients up to 14 weeks after recovery from SIPE and did not ask the patients about their symptoms, focusing only on measures of cardiopulmonary function [29]. The findings of a study of scuba divers showed a similar result; 6 months after admission for IPE, respiratory function, cardiac echography and exercise tolerance tests were all normal [34]. However, this study also did not report symptoms, which may be present despite undetectable changes in investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The single, very small, relevant study only studied patients up to 14 weeks after recovery from SIPE and did not ask the patients about their symptoms, focusing only on measures of cardiopulmonary function [29]. The findings of a study of scuba divers showed a similar result; 6 months after admission for IPE, respiratory function, cardiac echography and exercise tolerance tests were all normal [34]. However, this study also did not report symptoms, which may be present despite undetectable changes in investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In another report of 22 French healthy divers with IPE, 5 were found to have elevated troponin and brain natriuretic peptide plasma levels, without, however, electrocardiographic or echocardiographic disturbances. 3 The exact mechanism of RMD in the present study was not clearly elucidated. However, we propose that its development in the pattern of IPE might result from acute sympathetic activation and tissue hypoxia related to the reduction of oxygen delivery through the alveolareendothelial membrane, because clinical and functional recovery of the cardiac abnormalities occurred within days with no evidence of coronary artery disease.…”
Section: Discussionmentioning
confidence: 82%
“…18 In the present study, the water temperature was relatively low, with mean values consistent with other series of IPE. 3 The small water temperature range recorded between the incidental dives largely explains the lack of a significant influence of this parameter as predictor of cardiac injury in our divers. Finally, our data revealed that the release of natriuretic peptides, commonly used as biologic markers in the diagnosis and prognosis of heart failure, was closely related to the presence of myocardial abnormalities.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the coldness induced by water increases this hemodynamic strain (1, 2). The pressure difference causes blood circulation from the peripheral portion (extremities) to the central portion of the body (heart, lungs, and great vessels of the chest) and enlarges the venous return and cardiac preload (3,4). Relative pulmonary hypertension leads to an increased pressure gradient between the pulmonary capillaries and pulmonary parenchyma.…”
Section: Discussionmentioning
confidence: 99%